Artificial intelligence in the Brazilian Judiciary: safeguards, risks and new frontiers (Revista do Tribunal Regional Federal da 3ª Região, 2025)
This study investigates Brazil's pioneering adoption of artificial intelligence (AI) within the judiciary system, analyzing it as an essential strategy for the responsible regulation of these technologies. The central question of the analysis is: how to balance innovation and legal certainty in the use of AI in courts, ensuring safeguards without compromising efficiency and justice? Given the growing adoption of these tools, the research seeks to foster an institutional culture in which AI acts as support for judicial activities, being employed ethically, efficiently, and securely, aligned with the state's commitment to guaranteeing rights and protecting human dignity. The reflection includes essential safeguards (guardrails), high-risk applications, and emergency mechanisms (kill switches). Based on hearings by the National Council of Justice (CNJ) and documentary research, the study concludes that Brazil, through robust guidelines and innovative practices, can become a global reference in judicial AI regulation.
Keywords: artificial intelligence; Judiciary; regulation; governance; human dignity